Lone rangers : women on New Zealand county council : a thesis presented in partial fulfilment of the requirement for the degree of Master of Arts in History at Massey University - Lane, Sue (Massey University, 2004)
Soon after being elected as a Matamata county councillor early in the 1980s, I visited my parents. My father, who had immigrated from England as a 20 year old but still retained some of the British class-consciousness from which he had sought to escape, was quite pleased to have a member of the family in a role that he saw as 'aristocracy'. On this occasion, Brian Talboys, a friend of my father's and at that time Deputy Prime Minister, was also visiting and Dad took the opportunity to proudly announce that his daughter had joined the political elite, being the first and only woman elected to this council. Mr Talboys pondered for a minute and said "Goodness! Did you have a shortage of pain in your life? The Matamata County Council must be the last bastion of male chauvinism." This was definitely not the reaction Dad had expected, but those words and the grin with which they were delivered - stayed with me through many a long and difficult council meeting. It certainly impressed me that an experienced politician, and particularly a male one, should make that comment. In light of my subsequent experience, and my knowledge of the experiences of other women councillors I knew at the time, I wonder if county councils were indeed the 'last bastion of male chauvinism', or simply a reflection of their times. And if they were not typical of the times, what made them different and how was that difference manifest? This study seeks to place the experience of women on county councils in the context of the times. Was their treatment different from that experienced by rural women in general and by women on urban councils? What effect did they have? Did they make any difference in the council chamber, or to council decisions? Did they see a need for change, and have any success in achieving it? And of course along with all these questions goes the 'if so, how?', and 'if not, why not?' [FROM INTRODUCTION]
Keywords: New Zealand; Women county council members; Women in politics; Local Government